Statistical Analysis of Clinical Data on a Pocket Calculator Statistics on a Pocket Calculator - Cleophas, Ton J.; Zwinderman, Aeilko H.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The core principles of statistical analysis are too easily forgotten in today$1 (Bs world of powerful computers and time-saving algorithms. This step-by-step primer takes researchers who lack the confidence to conduct their own analyses right back to basics, allowing them to scrutinize their own data through a series of rapidly executed reckonings on a simple pocket calculator. A range of easily navigable tutorials facilitate the reader$1 (Bs assimilation of the techniques, while a separate chapter on next generation Flash prepares them for future developments in the field. This practical volume also contains tips on how to deny hackers access to Flash internet sites. An ideal companion to the author$1 (Bs co-authored works on statistical analysis for Springer such as Statistics Applied to Clinical Trials, this monograph will help researchers understand the processes involved in interpreting clinical data, as well as being a necessary prerequisite to mastering more advanced statistical techniques. The principles of statistical analysis are easily forgotten in today$1 (Bs world of time-saving algorithms. This step-by-step primer takes researchers back to basics, enabling them to examine their own data through a series of sums on a simple pocket calculator.s
Keywords: Medicine; Chemistry; Pharmacy; Computer science; Life sciences; Biomedicine; Biomedicine general; Chemistry/Food Science, general; Pharmacy; Medicine/Public Health, general; Computer Science, general; Life Sciences, general